2020
DOI: 10.1104/pp.20.00373
|View full text |Cite
|
Sign up to set email alerts
|

A Chlorophyte Alga Utilizes Alternative Electron Transport for Primary Photoprotection

Abstract: The green alga Desmodesmus armatus is an emerging biofuel platform that produces high amounts of lipids and biomass in mass culture. We observed D. armatus in light-limiting, excess-light, and sinusoidal-light environments to investigate its photoacclimation behaviors and the mechanisms by which it dissipates excess energy. Chlorophyll a/b ratios and the functional absorption cross section of PSII suggested a constitutively small light-harvesting antenna size relative to other green algae. In situ and ex situ … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 67 publications
0
9
0
Order By: Relevance
“…To limit noise on the exchange rates graphic, data shown in (D) are integrated with a sliding average of 30 s wide. study the link between CO 2 fixation and non-photochemical quenching of chlorophyll fluorescence (Sültemeyer et al, 1989;Fratamico et al, 2016;Ware et al, 2020). Furthermore, in conditions where the use of 18 O 2 is not possible (e.g.…”
Section: Assessment Of Photosynthetic Oxygen Exchangementioning
confidence: 99%
See 1 more Smart Citation
“…To limit noise on the exchange rates graphic, data shown in (D) are integrated with a sliding average of 30 s wide. study the link between CO 2 fixation and non-photochemical quenching of chlorophyll fluorescence (Sültemeyer et al, 1989;Fratamico et al, 2016;Ware et al, 2020). Furthermore, in conditions where the use of 18 O 2 is not possible (e.g.…”
Section: Assessment Of Photosynthetic Oxygen Exchangementioning
confidence: 99%
“…Gas exchange measurements, chlorophyll fluorescence (Maxwell and Johnson, 2000), and electrochromism measurements (Bailleul et al, 2010) are the three main tools available to measure photosynthetic activity in microalgae and cyanobacteria on intact organisms. Simultaneous measurements of gas exchange by MIMS and chlorophyll fluorescence have allowed for correlating energy dissipation processes with CO 2 and O 2 photoreduction occurring during photosynthesis (Sültemeyer et al, 1989;Burlacot and Peltier, 2018;Ware et al, 2020). However, our understanding is still limited by the functional redundancy of many mechanisms and their interaction with cryptic mechanisms such as cyclic electron flow, which are not easily experimentally accessible.…”
Section: Future Developments and Perspectivesmentioning
confidence: 99%
“…Membrane inlet mass spectrometry was measured similarly to (Broddrick, Du, et al., 2019 ) and (Ware et al., 2020 ). Samples corresponding to 4 μg chlorophyll a ml −1 were collected and resuspended in fresh f/2 media.…”
Section: Methodsmentioning
confidence: 99%
“…Here we coin the term excess electron transport (EET) as an additional important physiological feature at the intersection of photophysiology and bioengineering. This comprises several components that act either as shunts within the ETC (Jallet, Cantrell, & Peers, 2016 ; Ware et al., 2020 ) or downstream of the photosynthetic machinery within the broader metabolic network. It relieves over‐reduction of the photosynthetic ETC by dispelling electrons generated by excess light (Jallet, Cantrell, & Peers, 2016 ).…”
Section: Introductionmentioning
confidence: 99%
“…The shade-tolerant species such as Picea glauca , Abies balsamea and Abies lasiocarpa exhibit low P max , light saturating/compensation points (LSP/LCP) and dark respiration rates ( R d ) ( Valladares and Niinemets, 2008 ). Several studies have shown that the shade-tolerant species not only need to improve the efficiency of light energy utilization under low light, but also to strengthen the dissipation of excess light energy under high light condition ( Kim et al., 2020 ; Ware et al., 2020 ). The quantum yield of photosystem II (PSII), photosynthetic electron transport and photochemical quenching are increased in shade-tolerant species Bletilla striata exposed to a sudden transition from low to high light ( Yang et al., 2019a ).…”
Section: Introductionmentioning
confidence: 99%